Managing frozen foods - Kennedy, Chris (Woodhead Publishing in food science and technology., 2000)
An overview of frozen food technology and processes of the supply chain from the farm to the freezer of the consumer. Specialists in each field cover the particular concerns involved in freezing fruit, vegetables, meat, and fish.